SOS Games as an Alternative Game for Warming Up in Sports - Touvan Juni Samodra; Uray Gustian; Astiati Astiati (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2021)
This study aimed to test the SOS game used as a means to warm up. SOS games were usually played on paper. The trial game consists of 3 different levels. This game could be used as a movement activity to warm up. With some modifications, this game was tested. The trial was conducted on junior high school students, totaling 40 students. The data was obtained by measuring the pulse. Pulse was measured by counting the pulse in the neck for 10 seconds. The calculation result is multiplied by 6 to determine the number of pulses per minute—data analysis by comparing the measurement results with heating criteria based on age. The results showed that the first trial had a pulse rate of 142. Based on trial with 40 samples each at level 1, 140 level 2, 143, and level 3, 143 beats per minute. All of these pulses were in the exercise pulse. So it can be recommended that this game be used for heating purposes.